Gambaran Kepuasan Pendonor Darah terhadap Pelayanan Petugas Seleksi Donor Darah di UDD PMI Kota Yogyakarta Tahun 2022: Gambaran Kepuasan Pendonor Darah terhadap Pelayanan Petugas Seleksi Donor Darah di UDD PMI Kota Yogyakarta Tahun 2022 - rudina azimata rosyidah (Politeknik Kesehatan Bhakti Setya Indonesia, 2022)
Donor satisfaction is a person's feelings of pleasure or disappointment after comparing the services provided by the officers who are in accordance with their expectations. Donor satisfaction in relation to the services of donor selection officers can be measured based on 5 dimensions, namely responsiveness, reliability, assurance, empathy, and tangible. The purpose of this study was to assess the satisfaction of blood donors with the services of donor selection officers based on the dimensions of responsiveness, reliability, assurance, empathy, and tangible. This research is a descriptive type of research that describes the satisfaction of blood donors with the services of donor selection officers at UDD PMI Yogyakarta City in 2022. The research sample is blood donors at UDD PMI Yogyakarta City with accidental sampling method with a sample of 100 respondents and data analysis using a computer program with univariate analysis. Based on the research data, it was found that the majority of respondents were male, namely 75%. Based on the age of the most at the age of 25-44 years, namely 40%. Based on the most recent education S1/S2/S3 which is 48%. Based on the most occupations, private employees are 31%. The results of research on blood donor satisfaction with the services of donor selection officers at UDD PMI Yogyakarta City in 2022 showed that the perception of blood donor satisfaction based on the responsiveness dimension was 90.06%, the reliability dimension was 91.53%, the assurance dimension (assurance) 88.08%, the dimension of attention (emphaty) 89.66%, and the dimension of physical appearance (tangible) 68.93%. So that the average percentage of blood donor satisfaction with donor selection officers at UDD PMI Yogyakarta City in 2022 as a whole is 85.80% with a very satisfied classification.